Perceptions on the ideal masculinity and clothing among selected male students - Go, Thompson Alec B.; Caragay, Kristyn T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
There is limited research on how clothing communicates masculinity among Filipino men. The main objective of the study was to describe how clothing is used by selected Filipino male students in conforming to their perceived ideal masculinity based on the ideal sets of masculinity traits and clothing of masculinity, which emerged from the review of related literature. Survey questionnaires were distributed among 135 male undergraduate students in the University of the Philippines Diliman. They confirmed the presence of the six ideal sets of masculinity traits and clothing of masculinity in Philippine society "Mature, Responsible, Capable, and Industrious", "Straight, Rugged, Unemotional, and Firm", "Simple, Casual, Unflashy, and Straightforward", "Sporty, Competitive, Muscular, and Strong", "Dominant, Aggressive, Authoritative, and Tough", and "Well-groomed, Neat, Presentable, and Handsome". The study also showed that the significant sources of information about the ideal traits of masculinity were their family, their friends, and the media; and that the majority of the respondents (59%) conform through clothing in order to be respected, to be taken seriously, to look smart, and to be handsome. Afterwards, 12 of the respondents who conform to their perceived ideal of masculinity were interviewed. They indicated wearing the following clothing in order to conform: neutral- or dark-colored clothing; clothing with the normal type of fit and length; and clothing pieces like long sleeve polos, button down shirt, polo shirts, t-shirts, pants, slacks, jeans, chino pants, shorts, and chino shorts; and wristwatches. The study shows that society imposes ideal traits of masculinity, which is interpreted differently by different people, and that clothing may affect peoples perception of it. Moreover, when you conform to it through clothing, you exhibit the masculinity traits that accompany it as well.
submitted June 2017
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Men's clothing -- Philippines; Men's clothing -- Symbolic aspects